A review on anti-nutritional factors: unraveling the natural gateways to human health - Salim, Rehana; Nehvi, Iqra Bashir; Mir, Rakeeb Ahmad; Tyagi, Anshika; Ali, Sajad; Bhat, Owais M. (Frontiers in Nutrition, 2023)
Humans are constantly facing multiple health challenges from both communicable and non-communicable diseases that significantly affect their health. Additionally, drug resistance or failure has made the situation even worse and poses serious challenges for researchers to develop new drugs. Hence, to address these problems, there is an urgent need to discover and develop timely and long-term-based therapeutic treatments from different sources. One such approach is harnessing the potential of plant secondary metabolites. Plants have been utilized for therapeutic purposes in addition to being used for nutritional benefits. In the last two decades, plant-based drug developments have been one of the effective means of treating human diseases owing to their multiple functions. More recently, anti-nutritional factors (ANFs) have emerged as one of the important targets for novel plant-based drug development due to their multifaceted and potential pharmacological properties. However, their anti-nutritional properties have been the major setback for their limited success in the pharmacological sector. In this review, we provide an overview of ANFs and their beneficial roles in preventing human diseases with multiple case studies. We also highlight the recent developments and applications of ANFs in the food industry, agriculture, and pharmaceutics with future perspectives. Furthermore, we evaluate meta-analyses on ANFs from the last 30 years in relation to their function in human health benefits. This review is an endeavor to reevaluate the merit of these natural compounds and explore their potential for both human and animal health.